PENENTUAN NILAI OPSI EROPA DENGAN PEMBAYARAN DIVIDEN PADA WAKTU YANG TELAH DITENTUKAN - Purwandari, Diana
Fluctuations in stock prices lead stock trading risk. An alternative options to reduce the risk in stock trading. European option is a financial contract that gives the right, but not the obligation, to the holder, to buy or sell the underlying asset of the writer at the maturity date at a price specified. Option price valuation models are widely accepted in the field of finance is the Black-Scholes model. The purpose of this study is to determine the value of the European call option and the effect of dividend distribution through Black-Scholes model, determine the value of the European call option with dividend payments at a predetermined time, and determine the value of the lower limit and upper limit accurate than the European call option with payment dividend at a predetermined time. Value of the European call option with dividend payments at a predetermined time obtained using numerical integration with Simpson method of 12.6388. The calculation of the value of the lower limit and upper limit of the European call option that is accurate by using MATLAB software that gives results lower limit of the European call option at 12.6385 and the upper limit of the European call option at 12.6388